SEBUAH TINJAUAN EMPIRIS TERHADAP PROFITABILITAS, PELUANG INVESTASI KEPEMILIKAN MANAJERIAL DAN KEBIJAKAN LEVERAGE - Dananti, Kristyana - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Profitability is the net result of various policies and decisions of investors in capital markets. The higher portion of funds available to finance operations and investment opportunities that come from retained earnings then the level of leverage of the smaller companies. A company that has a high investment opportunity, will try to fill it by using the retained earnings of the company. If the investment exceeds retained earnings, closed with funds derived from debt so that the level of leverage increases. On the other hand, managers tend to use debt rather than to maximize corporate value, but for the sake opportunistic manager. This creates the risk of corporate bankruptcies increased, so the agency cost of debt is increasing. Agency cost of debt is higher will be the effect on the decline in value of the company. With the ownership of shares by the manager then the manager will have direct benefits for its decision. More and more managers have shares in a company the more diminished the company's debt. This study aims to examine the influence of profitability, investment opportunities, and managerial ownership of the policy leverage. Using the population of manufacturing companies listed on the Stock Exchange 2009 based on purposive sampling period, with the criteria that companies sampled have positive earnings during the period of 2009 and the company shares owned by management during the period 2009 samples acquired 41 companies. Analysis tools used to prove the hypothesis using multiple regression models by testing the significance of the results obtained by the classical assumption F count greater than 5%, so the influence of profitability, investment opportunities and managerial ownership of the policy leverage is not significant. Keywords: policy leverage, profitability, investment opportunities and managerial ownership